BRAIN ATROPHY AND DISEASE-FREE STATUS OVER 4 YEARS OF FREEDOMS STUDY. Issue 10 (9th September 2014) - Silber, Eli; Radue, Ernst-Willhelm; De Stefano, Nicola; O'Connor, Paul; Piani-Meier, Daniela; Francis, Gordon; Tomic, Davorka; Kappos, Ludwicg
Abstract : Objective: Evaluate the relationship between Disease-Free (DF) status and brain atrophyover 4 years from the fingolimod phase III FREEDOMS study and extension. Method: DF-status was defined as the maintained absence over 0–48 months of all the following: confirmed disability progression, confirmed relapses, new Gd-enhancing T1-lesions and new/enlarged T2-lesions; patients having any one or more of these measures were defined as not DF (nDF). In these posthocanalyses, Percentage Brain Volume Change (PBVC) during months 0–12, 0–24, 0–36 and 0–48 was dichotomized by DF-status at month-48 (DF or nDF) in the overall study population (OSP) and by treatment-group (fingolimod 0.5 mg; combined fingolimod 0.5 and 1.25 mg; and placebo-fingolimod patients [Plc-fingolimod]). Results: In the OSP, DF-patients had lower PBVC during the core-study and extension, versus nDF patients (DF/nDF): month 0–12, −0.17%/−0.60%; month 0–24, −0.53%/−1.14%; month 0–36, −0.94%/−1.52%; month 0–48−1.36%/−2.08%. Continuously-treated fingolimod 0.5mg patients had lower PBVC over month 0–48 versus switch patients: DF (fingolimod/Plc-fingolimod; % difference): −1.12%/−1.66%; 38.8%; nDF: −1.77%/−2.54%; 35.7%. Conclusions: Patients DF over 48-months experienced less brain volume loss (BVL) than nDF patients over 4-years. A treatment delay of 2 years with fingolimod was associated with more BVL.